The Effect of THK-Based Interactive Indonesian Language Electronic Student Worksheet on the Reading Literacy Skills of Fourth-Grade Students at SDN 4 Banyuasri - I Nyoman Sudiana; I Komang Sugi Partawan; Ida Ayu Made Darmayanti; I Made Hendra Sukmayasa; Ni Nyoman Kurnia Wati (CV. Media Inti Teknologi, 2025)
Background: Literacy issues in Indonesia represent a serious problem and are a primary focus for both the central and local governments. Reading literacy, in particular, must be addressed from an early stage, starting at the elementary school level.Aims: This study aims to tackle elementary students' reading literacy challenges by implementing Tri Hita Karana (THK)-based Interactive Indonesian Language Electronic Student Worksheet (IIESW). The THK-based Interactive electronic student worksheet was chosen because it contains engaging reading materials, animated videos, and interactive quizzes that make learning enjoyable for students.Method: This research employs a quasi-experimental method, conducted in three stages: preparation, implementation, and conclusion. The population, which also served as the sample, consisted of 38 students. Data collection was carried out using tests, while data analysis involved quantitative descriptive analysis and inferential analysis using one-way ANOVA.Results: Based on the research that has been conducted, it was found that the use of THK-based IIESW has a significant influence on students' reading literacy skills, with a calculated f of 118.058 and a significance of 0.00.Conclusion: Therefore, it can be concluded that there is a significant influence of THK-based IIESW on the reading literacy skills of class IV students at SDN 4 Banyuasri.